Spirit Tech: The Brave New World of Consciousness Hacking and Enlightenment Engineering. By Wesley J. Wildman and Kate StocklyReligion and the Technological Future: An Introduction to Biohacking, Artificial Intelligence, and Transhumanism. By Calvin Mercer and Tracey J. Trothern - Singler, Beth (Journal of the American Academy of Religion, 2022)
Some might even consider religion itself a technology, a human-created device for navigating our world, or a technology of the self in the Foucauldian sense. Again, as in the introductory line from I Religion and the Technological Future i , it is the very existence of religion that is claimed to be at stake: "Are new spiritual technologies compatible with the religious institutions that have acted as gatekeepers for enlightenment for the past twenty-five hundred years? Or will those religions dismiss these technologies as inauthentic, forcing the new wave to deem old religions obsolete?" (258).